Comparison of consumer preferences of dog food products between Thailand and Singapore using choice-based conjoint analysis - Phaosathienpan Sarun; Leong Jasmine; Tengpongsathon Kallayanee (My University, 2014)
This research investigated the difference in consumer perception of dog food products between Thais and Singaporeans using ChoiceBased Conjoint Analysis (CBC). The empirical analysis used consumer-level questionnaires to elicit the information (n=184 for Thai consumers and n = 141 for Singaporean consumers) with regards to four attributes (packaging format, price, brand quality and nutrition) with three predefined elements for Thai consumers (packaging format: canned, pouch, dry; price: 85 Baht, 135 Baht, 165 Baht per kg; brand quality: unbranded, commercial, premium; nutrition: fulfilled, silky fur and skin condition, dog’s preference) and for Singaporean consumer (packaging format: canned, pouch, dry; price: < S$5, S$5-$7, > S$7 per kg; brand quality: supermarket, premium, holistic; nutrition: general, specific, dog’s preference). The results of conditional logistic regression suggested that “premium”, “dry”, “silky fur and skin condition” were important elements for Thai consumers, while “dry”, “holistic brand” and “specific nutrition” were important elements for Singaporean consumers. The “price” attribute did not contribute significantly to consumer preferences in both countries. In addition, CBC showed an overestimation in values of elements of dog food products. This may have resulted from respondents having focus on their preferred elements and ignored other elements. It was also found that the “dry” and “holistic” elements were the main dominating attributes for Singaporean and Thai consumers respectively. The comparison of the CBC results between both countries has helped to identify the potential profile of dog food products.
Keywords: Conjoint Analysis; Thais; Economic and Environmental Valuation